2013
DOI: 10.1371/journal.pone.0082301
|View full text |Cite
|
Sign up to set email alerts
|

A Role for Myocilin in Receptor-Mediated Endocytosis

Abstract: Myocilin is a broadly expressed protein that when mutated uniquely causes glaucoma. While no function has been ascribed to explain focal disease, some properties of myocilin are known. Myocilin is a cytoplasmic protein that also localizes to vesicles specifically as part of a large membrane-associated complex with properties similar to the SNARE machinery that function in vesicle fusion. Its role in vesicle dynamics has not been detailed, however myocilin intersects with the endocytic compartment at the level … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 62 publications
(69 reference statements)
1
12
0
Order By: Relevance
“…Both exosomes and melanosomes are components of the endosomal compartment, and in both cases, GPR143 signaling appears to inhibit the membrane fusion of that compartment, but with different outcomes. In previous studies, we have shown that GPR143 signaling recruits the cytoplasmic protein myocilin to the endosomal compartment, where it is released from the cells on the surface of exosomes [29,52,53]. This observation provides direct evidence that GPR143 signaling causes cytoplasmic protein translocation to the exosome prior to release.…”
Section: Gpr143 Signalingsupporting
confidence: 52%
“…Both exosomes and melanosomes are components of the endosomal compartment, and in both cases, GPR143 signaling appears to inhibit the membrane fusion of that compartment, but with different outcomes. In previous studies, we have shown that GPR143 signaling recruits the cytoplasmic protein myocilin to the endosomal compartment, where it is released from the cells on the surface of exosomes [29,52,53]. This observation provides direct evidence that GPR143 signaling causes cytoplasmic protein translocation to the exosome prior to release.…”
Section: Gpr143 Signalingsupporting
confidence: 52%
“…Thus, caveolin-mediated endocytosis is one mechanism by which TM cells can alter the catabolism of ECM components and may contribute to the pathological changes that are observed in glaucomatous TM. A recent study showed that the archetypal glaucoma gene, myocilin, may also be involved in receptor-mediated endocytosis (McKay et al, 2013). …”
Section: Potential Mechanisms Leading To Ecm Changes In Glaucomatous Tmmentioning
confidence: 99%
“…Alternative hypotheses have been proposed to explain the deleterious cellular effects of MYOC mutations, such as altered association kinetics and co-localization with proteins in the endocytic pathway (e.g. (Hardy et al, 2005; McKay et al, 2013)).…”
Section: Myocilinmentioning
confidence: 99%